The Effect of Animated Video Traditional Games Learning Media on Kindergarten Children’s Mathematical Abilities: An Experimental Study - Amini Nur, Nabila; Nurhafizah Nurhafizah; Yaswinda Yaswinda; Setiyo Utoyo (Institut Agama Islam Negeri Madura, 2026)
This study aims to analyze the influence of traditional game animation video learning media on the mathematical abilities of children aged 5–6 years at Oswald Siahaan Kindergarten. This study uses a quantitative approach with an experimental method. The experimental design used is quasi-experimental with a one-group pretest–posttest model. The population in this study consists of all children in Group B at Oswald Siahaan Kindergarten, totaling 20 children, with the sampling technique being a saturated sample. Data collection was carried out thru structured observation methods to measure children's mathematical abilities, including understanding number concepts, simple arithmetic operations, recognition of geometric shapes, and concepts of measurement. Data analysis was conducted by comparing pretest and posttest results using the paired sample t-test. The research results using the paired sample t-test obtained an Asympsig (2-tailed) value of 0.000 < 0.05. this means there is an improvement in children's mathematical abilities after using traditional game animation video media. These findings indicate that traditional game animation videos have a positive and effective impact on improving early childhood mathematical abilities.